1994
DOI: 10.1207/s15328023top2101_12
|View full text |Cite
|
Sign up to set email alerts
|

Getting the Most from PsycLIT: Recommendations for Searching

Abstract: PsycLIT, the optical disc counterpart of Psychological Abstracts, has greatly enhanced access to the world's psychological literature. Because researchers often do not fully understand indexing techniques and system protocols, however, retrieval via PsycLIT can be inconsistent. This article makes suggestions for improving search outcomes. Recommendations include knowing the scope of the data base, distinguishing between keyword and controlled vocabulary searches, using indexing principles to improve retrieval,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…unlv.edu/faculty/kkemtes,.jCHE). Note that for some databases, such as PsyciNFO, helpful search guides have been published (e.g., Gosling, Knight, & McKenney, 1990;Joswick, 1994) .…”
Section: Databases and Online Journalsmentioning
confidence: 99%
See 1 more Smart Citation
“…unlv.edu/faculty/kkemtes,.jCHE). Note that for some databases, such as PsyciNFO, helpful search guides have been published (e.g., Gosling, Knight, & McKenney, 1990;Joswick, 1994) .…”
Section: Databases and Online Journalsmentioning
confidence: 99%
“…They also fo und that students misperceived the efficacy of their search, often believing that they had conducted a thorough review when the outcome demonstrated otherwise. This misperception may be attributable to a lack of understand ing of databases and poor development of search strategies (Joswick, 1994) .…”
mentioning
confidence: 99%